Risiko Pernikahan Dini dan Konvergensi Pencegahan Stunting Pada Remaja di Desa Karampi Kecamatan Langgudu Kabupaten Bima - darmin darmin; Walliyudin Walliyudin; Gufran Gufran; Alkhair Alkhair; M. Noris; Muammar Iksan; Dea Zara Avila; Nur Husnul Khatimah; Muh. Fitrah (Cv. Utility Project Solution, 2023)
The issue of early marriage and stunting is currently a national issue because it is related to the quality of human resources in the future, so there is a need for handling and prevention efforts. The purpose of this community service activity is to prevent early marriage and convergence to prevent stunting in adolescents. Socialization and counseling on the risks of early marriage and convergence for stunting prevention were carried out in Karampi Village, Langgudu District, Bima Regency, West Nusa Tenggara Province. The community service program process is carried out consisting of 3 stages which include the data collection stage, the socialization and education stage, as well as the reflection and evaluation stage. The community service sample includes 63.46% female participants and 36.53% male participants. Data analysis used a paired sample t test to determine the level of public understanding before (pretest) and after (posttest) socialization and counseling. The results of community service show that the level of understanding after outreach and counseling on the risks of early marriage is around 85.96% and the convergence for stunting prevention is around 89.81%.